(untitled) (Research, Society and Development, 2024)
The canine spine is a vertebral structure composed of cervical, thoracic, lumbar, sacral, and caudal vertebrae, providing support, protection to the spinal cord, and flexibility to the body. However, vertebral malformations in dogs are diverse and compromise the normal development of the vertebrae, potentially leading to a range of health and well-being issues for these animals. Based on this, this paper aims to describe the anatomy of the canine spine and compare it with the anatomical changes found in some vertebral malformations, as well as their clinical implications, through a literature review. Among the most important vertebral malformations in dogs, hemivertebra, spina bifida, and Wobbler syndrome stand out. Hemivertebra is a vertebral malformation in which a vertebra develops incompletely or in a wedge shape, resulting in abnormal curvatures of the spine, such as scoliosis or kyphosis. Spina bifida is a congenital defect where the vertebral column does not close completely during embryonic development, leaving an opening that can expose the spinal cord. Wobbler syndrome, on the other hand, is a condition characterized by spinal cord compression in the cervical region, caused by vertebral malformations, leading to ataxia, weakness, and coordination problems. Thus, early identification of malformations is crucial for proper management and the implementation of therapeutic interventions that can improve function and/or quality of life for the patients.